PENYELESAIAN KASUS SERTIFIKAT HAK ATAS TANAH CACAT HUKUM MENURUT HUKUM PERTANAHAN DI INDONESIA (Studi Kasus Putusan Nomor: 46/G/2019/PTUN-SRG) - Agnelia Andini; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2022)
The plaintiff submits a measurement request to the defendant. However, at the location of the plaintiff's proposed land there have been four certificates of land rights issued by the defendant. The plaintiff filed a lawsuit against the four State Administrative Officer Decrees. Basically, the plaintiff and the previous land owner have never registered the land they own, so the land should not have been certified. The four certificates that were issued also had defects and were not based on the right basis of rights which according to Indonesian land law should not have been issued. This research is a type of descriptive normative research. Sources of data used are primary, secondary, and tertiary data. The results of this study indicate that the defendant was negligent and careless in carrying out the responsibilities as a public servant in issuing certificates of land rights, resulting in the issuance of certificates of land rights that were flawed. The Defendant is administratively and civilly responsible. The conclusion from this study is that the plaintiff was harmed by the defendant who was the party authorized to issue the certificate.